Two stage repair of hypospadias - Din, Ikram ud; Younas, Muhammad (Journal of Postgraduate Medical Institute, 2011)
To assess the results of two stage repair of hypospadias. This a prospective study was conducted in the department of paediatric surgery KTH, Peshawar from September 2001 to September 2003. Forty five patients were included in this study. All patient with proximal and distal hypospadias with or without chordee, circumcised cases and those who needed revision surgery were selected fro two stage repair. In stage I splitting of the glans and grafting of the donor area with full thickness skin graft was done. In stage 2 the tubularization of the graft and covering the repair with a waterproofing layer of fascia was done 6 - 8 months later. From our experience we conclude that two stage reapir of hypospadias offers unique versatility, excleent reliablity and a sophistication of function and aesthetics is achieve with two stage repair.